Light Induced Processes for the Synthesis of Polymers With Complex Structures - Durmaz, Yasemin Y.; Tasdelen, M. Atilla; Aydogan, Binnur; Kahveci, Muhammet U.; Yagci, Yusuf (Springer Netherlands, 2009)
Light induced reactions are based on the absorption of light that excites the electrons of a molecule and can, under favorable circumstances, lead to dissociation, isomerization, abstraction, electron or energy transfer, and bond formation. These reactions have been the subject of many studies in various fields including organic chemistry, molecular biology, electronics etc. Light induced reactions can advantageously be utilized in the field of polymer chemistry. Among them, light induced polymerization is of enormous commercial importance. Techniques such as curing of coatings on wood, metal and paper, adhesives, printing inks and photoresists are based on photopolymerization. There are some other interesting applications, including production of laser video discs and curing of acrylate dental fillings. In this chapter, general methods for the light induced polymerization processes involving radical and ionic reactions are described. Special emphasize is devoted to their application to more complex macromolecular structures such as block, graft and star copolymers, and polymer nanocomposites based on clay and metal.